PENGARUH E-SPT PAJAK PENGHASILAN DAN PEMAHAMAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Sabil .; Amin Setio Lestiningsih; Dwiyatmoko Pujiwidodo (Universitas Sangga Buana, 2018)
Improving the quality of tax service to the taxpayer the Directorate General of Taxes apply electronic system (e-SPT) in tax reporting. The purpose of this study is to determine the effect of the application of e-SPT Personal PPH and the understanding of taxation on taxpayer compliance. This research uses survey method and multiple regression analysis. Data collection is done by using questionnaires distributed to individual taxpayers. Based on the results of research can be concluded that the implementation of e-SPT Personal PPH and understanding taxation significantly influence 55.3% of taxpayer compliance and 44.7% influenced by other factors.